The P15-loop of Escherichia coli RNase P RNA is an autonomous divalent metal ion binding domain. - Kufel, J (1998)
We have studied the structure and divalent metal ion binding of a domain of the ribozyme RNase P RNA that is involved in base pairing with its substrate. Our data suggest that the folding of this internal loop, the P15-loop, is similar irrespective of whether it is part of the full-length ribozyme or part of a model RNA molecule. We also conclude that this element constitutes an autonomous divalent metal ion binding domain of RNase P RNA and our data suggest that certain specific chemical groups within the P15-loop participate in coordination of divalent metal ions. Substitutions of the Sp- and Rp-oxygens with sulfur at a specific position in this loop result in a 2.5-5-fold less active ribozyme, suggesting that Mg2+ binding at this position contributes to function. Our findings strengthen the concept that small RNA building blocks remain basically unchanged when removed from their structural context and thus can be used as models for studies of their potential function and structure within native RNA molecules.